A WORLD PARLIAMENT : Governance and Democracy in the 21st Century - Leinen, Jo; Bummel, Andreas (Democracy Without Borders, 2024)
For the first time in history, all people worldwide are linked together in a shared civilization that spans the entire Earth. Humanity now has a common destiny. Global challenges such as war, poverty, inequality, climate change, and environmental destruction are overwhelming nation-states and today’s international institutions. Even the best policies are futile if there are no appropriate political structures in place to implement them. Autocracy and nationalism further undermine global collaboration. But the desire for freedom and change is unabated